The Need of Education On Religious Tolerance Among The Buddhist Minority In Indonesia - Santacitto Sentot; Aryanto Firnadi (STAB Kertarajasa, 2022)
Throughout history, Indonesia has faced several violence out of which religious issues has most likely become the trigger for such violence. In attempt on building tolerance among religious communities, there are four questioning points that need to be dealt with: 1) what is the religious tolerance? 2) what are the causes for the arising of religious intolerance? 3) what is our response in facing intolerance acts from other religious communities? 4) what are our contributions in creating tolerance, unity, peace and harmony in the midst of religious diversity. This research attempts to discuss this subject matter comprehensively with reference to Buddhist’s canonical literature, with its main aim for educating Buddhist minority in Indonesia on the importance of religious tolerance. The education is greatly needed for two main reasons. The first reason is to make Buddhists minority in Indonesia understand clearly the Buddhist attitude on religious tolerance, thereby they would behave themselves wisely towards followers of other religions. Secondly, it is an attempt to protect them from violence or harassment that might be assaulted from other parties. For, by knowing how to deal and act wisely towards other religious communities, besides that they have taken part in creating tolerance and peace, they are actually protecting themselves. The idea is that protecting others, they protect themselves. From the study it is found that the violence in the society on the name of religion often happens due to the lack of tolerance among religious communities. Education on religious tolerance should be given to Buddhists in Indonesia to prevent other religious communities from treating Buddhists with intolerance, violence or harassment.